The origins of Moroccan Arabic formal education in Spain in the late eighteenth century: an instrument for diplomatic issues with Morocco - Salgado Suárez, Rosa (Anaquel de Estudios Árabes, 2021)
This article refers to a historical event, such as the signing of the Treaty of Friendship and Commerce between Spain and Morocco in 1767, to contextualize the origins of the history of the Moroccan Arabic formal education in Spain. In effect, the signature of this Treaty highlighted the need to train a staff of reliable translators and interpreters who provides mediation with neighbouring Morroco in matters of diplomacy. The improvised staff consisted of Spanish Arabists who learned Moroccan Arabic in Morocco itself thanks to the boost given by two important measures: 1798 pension plan and the establishment of an Arabic school in Tangiers in 1800. The first generation of Arabist experts in Moroccan Arabic was thus formed, who, in addition to government translators-interpreters, became the authors of the first materials for its teaching.